THE SIGNIFICANCE OF FANON’S POLITICAL THEORY TO PAN AFRICANISM - Adekunle Alaye (International Studies Journal)
The study explores the contributions of Frantz Fanon political theories towards the liberation of the African countries from the imperial invasion of the colonialists. Fanon personified ‘’Decolonization as the meeting of two forces, opposed to each other by their nature, which in fact owe their originality to that sort of sub-stratification which results from and is nourished by the situation in the colonies. He stressed further to say that ‘’we must archive revolutionary socialism all together everywhere, or else one by one we would be defeated by our colonial masters’’. The aphorism from Fanon, was actually to awake the consciousness of Africans and other European colonies to reject the imperial structures in their respective communities. This according to him was a ‘’divide and rule system’’ by the colonialists, to penetrate deeply into their colonies’ administrative structures.